MENINGKATKAN KETERAMPILAN MEMBACA GRAFIK MELALUI MEDIA GRAFIK TIMBUL PADA ANAK TUNANETRA KELAS XI SMA N 2 PAINAN - Dwi Septina Rahayu; Marlina Marlina (Universitas Negeri Padang, 2014)
Abstrack: This study discussed the improvement of skill of reading graph toward the blind child on class XI SMA N 2 Painan on Mathematics subject. Started from the observation that researcher found the blind child had not been able to read the chart, so after administered an observation with the target behavior and distinguished graphs, identified and read charts. The purpose of this research was to prove the media charts arise could improve the skill of reading graph in math subjects in blind children.This research used experimental approach in the form of single subject design (SSD) with multiple baselines cross variables design and research data analysis used a visual graph analysis technique.Data analysis indicated that baseline data differentiated the graphics for 3 days with a mean of level 3 and the trend horizontal directions and trends continued with intervention for 9 days with mean level 6, the trend increased and data change improved (+3). The identified baseline graph done in 5 days with a mean of level 0 and horizontal direction and trend continued with intervention for 7 days with a mean level 15,14 the trend increased and data change improved (+10). The chart baseline was read for 7 days with a mean of level 0 and horizontal direction trend continued with intervention in 5 days with a mean level of 15.4, the trend increased and data change improved (+13) and all the targets had overlap behavior data to 0%. The conclusion was that media graphic arise improved the skills of Reading Graphs on Mathematics subject for visually impaired or blind child on XI class SMA N 2 Painan. Based on the results of this research, hoped the teachers and Government presented the graph in the shape of embossed to be read by the visually impaired or blind students. Kata Kunci: reading graph; media chart arise; blind children.